Overweight and obesity in elementary schools in three villages of El Progreso, Guatemala - Gonzalez Alvarez, Ana (Kansas State University, 2021)
Introduction: Childhood obesity is a principal concern worldwide. There is limited information in Guatemala on risk factors for obesity in relation to school environments. The purposes of this study was to characterize the food environment around schools, and to assess if the prevalence of overweight and obesity in children is associated with schools. Methods: A cross-sectional study was conducted in four rural public schools within three villages of El Progreso, a Department of Guatemala. Anthropometric measures and sociodemographic information for 398 schoolchildren and their mothers was collected in 2018. Environmental audits of food outlets and food advertisements were completed for a 500 meter buffer around schools. One-way ANOVA was used to compare schools for overweight and obesity and variables regarding the food environment. Fisher’s Least Significant Difference post hoc tests were used to examine differences by schools. Last, a logistic regression was used to examine the mean differences between schools on overweight and obesity, adjusted for household income, child sex, and maternal education and age. Results: The overall percentage of overweight and obesity, ranged from 8.5% to 38.8% among the four schools. ANOVA showed a statistically significant difference between schools for overweight and obesity (p=0.039) and in the distance of food outlets (p=0.001) and food advertisements (p<0.001). The Fisher’s LSD test showed that school 2 had significantly lower prevalence of overweight and obesity than school 1 (M=-0.17, 95%CI: -0.31, -0.03), and school 3 (M=-0.197, 95%CI: -0.34, -0.06). Logistic regression showed that schools are associated with overweight and obesity (p=0.043), when adjusting for household income, child sex, and maternal education and age. A higher percentage of food outlets within 100 meters was found around school 1 (45.9%), followed by school 3 (42.6%), while a higher percentage of food advertisements was found within 300 meters of school 2 (50.0%). Overall, poor quality unhealthy foods were predominant and proximal to schools. Conclusion: More research is needed on obesity prevention in Guatemala—especially in rural communities—to enhance the creation and implementation of health and nutrition policies that promote healthy food environments around elementary schools.
Keywords: Overweight; Obesity; Food environment; Children; Guatemala